Mesenchymal stem cell-based therapy for autoimmune-related fibrotic skin diseases—systemic sclerosis and sclerodermatous graft-versus-host disease - Han Yang; Sousan Cheong; Yunfan He; Feng Lu (Stem Cell Research & Therapy, 2023)
Abstract Background Systemic sclerosis (SSc) and sclerodermatous graft-versus-host disease (Scl-GVHD)—characterized by similar developmental fibrosis, vascular abnormalities, and innate and adaptive immune response, resulting in severe skin fibrosis at the late stage—are chronic autoimmune diseases of connective tissue. The significant immune system dysfunction, distinguishing autoimmune-related fibrosis from mere skin fibrosis, should be a particular focus of treating autoimmune-related fibrosis. Recent research shows that innovative mesenchymal stem cell (MSC)-based therapy, with the capacities of immune regulation, inflammation suppression, oxidation inhibition, and fibrosis restraint, shows great promise in overcoming the disease. Main body This review of recent studies aims to summarize the therapeutic effect and theoretical mechanisms of MSC-based therapy in treating autoimmune-related fibrotic skin diseases, SSc and Scl-GVHD, providing novel insights and references for further clinical applications. It is noteworthy that the efficacy of MSCs is not reliant on their migration into the skin. Working on the immune system, MSCs can inhibit the chemotaxis and infiltration of immune cells to the skin by down-regulating the expression of skin chemokines and chemokine receptors and reducing the inflammatory and pro-fibrotic mediators. ​Furthermore, to reduce levels of oxidative stress, MSCs may improve vascular abnormalities, and enhance the antioxidant defenses through inducible nitric oxide synthase, thioredoxin 1, as well as other mediators. The oxidative stress environment does not weaken MSCs and may even strengthen certain functions. Regarding fibrosis, MSCs primarily target the transforming growth factor-β signaling pathway to inhibit fibroblast activation. Here, miRNAs may play a critical role in ECM remodeling. Clinical studies have demonstrated the safety of these approaches, though outcomes have varied, possibly owing to the heterogeneity of MSCs, the disorders themselves, and other factors. Nevertheless, the research clearly reveals the immense potential of MSCs in treating autoimmune-related fibrotic skin diseases. Conclusion The application of MSCs presents a promising approach for treating autoimmune-related fibrotic skin diseases: SSc and Scl-GVHD. Therapies involving MSCs and MSC extracellular vesicles have been found to operate through three primary mechanisms: rebalancing the immune and inflammatory disorders, resisting oxidant stress, and inhibiting overactivated fibrosis (including fibroblast activation and ECM remodeling). However, the effectiveness of these interventions requires further validation through extensive clinical investigations, particularly randomized control trials and phase III/IV clinical trials. Additionally, the hypothetical mechanism underlying these therapies could be elucidated through further research.